THE ROLE OF DAYAK BAKATI WOMEN IN KIUNG VILLAGE IN MAKING BIA AS A FORM OF MAINTAINING FOOD TRADITIONS - Ana, Jaklin; Elingsetyo Sanubari, Theresia Pratiwi; Wijaya, Firdhan Aria (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2021)
The role of the Dayak Bakati women in Kiung Village is very important in preparing the traditional maka'k dio pade ceremony. This tradition uses food products that are processed as complementary materials for carrying out traditional rituals. Purpose: This study aims to determine the role of Dayak Bakati women from Kiung Village in food processing to sustain food traditions and customs. Method: A qualitative approach with a direct interview technique was used. Results: The Dayak Bakati women live daily as farmers and fulfill household needs from garden and field products. This shows that they are closely related to nature, society, and customs. Conclusion: The Dayak Bakati women not only become housewives but also practicefarming and gardening to achieve food sovereignty. The improvement and fulfillment of food traditions relate to the food sovereignty of the community and the method of processing bia for the maka'k dio pade tradition. However, this tradition is rarely practiced due to the belief in individual religion, but thisis not the major reason for the decline. The maka'k dio pade is rarely carried out by the 2000s generation because they have migrated to study abroad. Keywords: Tradition, food sovereignty, the role of women